PENGARUH DEKSTRIN DAN GUM ARAB TERHADAP SIFAT KIMIA DAN FISIK BUBUK SARI JAGUNG MANIS (Zeamays saccharata) [The Effects of Dextrin and Arabic Gum on Chemical and Physical Properties of Sweet Corn (Zeamays saccharata) Milk-like Powder] - . Sutardi; Suwedo Hadiwiyoto; Constansia Ratri Nugroho Murti (Jurnal Teknologi dan Industri Pangan, 2010)
The aim of this research was to determine the effects of type and amount of binder on the chemical and physical properties of sweet corn milk-like powder. Sweet corn milk-like powder was prepared from sweet corn kernel extracted with water with ratio of water and kernel of 2:1 (v/w), then dehydrated by spray dryer. Dextrin and arabic gum in various amount i.e. 2.5;  5.0; and 7.5% (w/v), respectively were added to the sweet corn milk-like before drying, and control was also made. The reducing sugar and total sugar, protein, fat, and moisture content, and as well as bulk density, colour, and solubility of the powder were then analyzed. The chemical and physical properties of sweet corn milk-like powder with addition of dextrin and arabic gum in the amount of 2.5; 5.0; and 7.5% (w/v) were significantly different (p > 0.05). According to all aspects studied, sweet corn milk-like powder with addition of dextrin in the amount of 2.5% was the best product of all, which had reducing sugar of 5.00% (db); total sugar 17.01% (db); protein13.67% (db); fat 5.97% (db); moisture 5.38%; bulk density 0.47 g/cm3; and solubility of 93.70%.